THE MI GRAI NE- VERTI GO- PERI ODONTAL DI SEASE CONNECTION: EVIDENCE-BASED CASE AND VERIFICATION IN AN ANIMAL STUDY - Utomo, Haryono (Institute of Topical Disease Universitas Airlangga, 2010)
Recently, two CNS disorders, migraine and anxiety have been recognized as being commonly associated with dizziness (Vertigo).These associations may be an expression of an etiological relationship, for example, dizziness caused by migraine, or dizziness causedby anxiety and termed as MARD. Chronic dizziness may become more disabling during the added stress of a migraine headache orpanic attack. In addition, dizziness occurred comorbidly with both migraine headache and anxiety disorders. Even though the etiologyof migraine had been suggested from trigeminal nerve sensitivity and neurogenic inflammation, its linking to periodontal disease thatinnervated by the same nerve was still uncertain. However, an animal study revealed that Porphyromonas gingivalis lipopolysaccharidestimulation was able to increase neurogenic inflammation. A male patient suffered with symptoms mimicking MARD for years andconcomitantly had chronic periodontitis. Scaling and root planning combined with the assisted drainage therapy resulted in instantdisappearing of most of the symptoms. This case report is to propose the mechanism of periodontal disease involvement in theetiopathogenesis of migraine and vertigo which could be treated with periodontal treatment. Regarding to remarkable result, it wasconcluded that periodontal disease could be a source of neurogenic and immunogenic inflammation which if not treated periodicallycould perpetuate symptoms mimicking MARD.